Studies in Jainism - Marathe, M. P.; Kelkar, M. A., Mrs.; Gokhale, Pradīpa, 1953- (Pune, India : I.P.Q. Publications, 1984)
Proceedings of three seminars on Jaina logic and philosophy, 1975, Jaina logic, culture, and literature, 1977, and Jaina philosophy and modern scientific thought, 1979, organized by the Dept. of Philosophy, University of Poona.
English and Hindi.
Includes bibliographical references and index.
Keywords: Jainism -- Congresses